What do we know about the future of food systems innovation? - Mason-D'Croz, Daniel; Herrero, Mario; Kugler, Cody; Remans, Rosaline; Thornton, Philip K.; Zornetzer, Heather (International Food Policy Research Institute, 2025)
Innovations have been and will continue to be critical drivers of food systems and societal change.